Vitamin K: A potential Liver Cancer treatment way - Sofi a Dahlberg; Ulf Schött (Archives of Hepatitis Research - Peertechz Publications, 2017)
A review on different vitamin K1-3 effects on hepatocellular cancer and their tumour cell biology mechanism indicate possible synergistic treatment strategies. Monitoring of dysfunctional carboxylation of the vitamin K dependent coagulation factor II, with the commercial ELISA test PIVKA-II has been used as a hepatocellular cancer marker. Its relevance is also reviewed. Currently the PIVKA-II test has been withdrawn due to marketing reasons by Stago.